2013
DOI: 10.5812/asjsm.34242
|View full text |Cite
|
Sign up to set email alerts
|

Positive Effect of the Use of Accelerometry on Lifestyle Awareness of Overweight Hypertensive Patients

Abstract: Conclusion: Accelerometry allows to objectify PAL, and can be used to monitor improvement of variables strongly related to cardiovascular risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Moeini et al showed in their study that training programs help to broaden individuals’ awareness of physical activity [27]. A study by Stefani et al showed similar results [28]. …”
Section: Discussionmentioning
confidence: 89%
“…Moeini et al showed in their study that training programs help to broaden individuals’ awareness of physical activity [27]. A study by Stefani et al showed similar results [28]. …”
Section: Discussionmentioning
confidence: 89%
“…Lifestyle was assessed at the beginning of the program to evaluate the spontaneous physical activity [ 14 ]. An accelerometer (armband model MF-SW, display model DD100, SenseWear ® , BodyMedia ® , Pittsburgh, Pennsylvania, USA) on the non-dominant arm of the patients to be kept for one week.…”
Section: Methodsmentioning
confidence: 99%
“…The SAM is well validated and has an accuracy of 99% in detecting steps in intervals of 1 min [8, 9]. Other accelerometers have also shown that objective data can be collected to assess physical activity levels [10]. Patients were instructed to wear the SAM at the right leg lateral above the lateral malleolus for the whole day from getting up to going to bed and were asked to record the non-wear times.…”
Section: Methodsmentioning
confidence: 99%